THE EFFECT OF AUDIT QUALITY, RETURN ON ASSET, AND NET PROFIT MARGIN ON INCOME SMOOTHING WITH FINANCIAL LEVERAGE AS A MODERATION VARIABLE - Novi Darmayanti; Siti Shoimah; Tasya Lailatul Firdaus (J-MACC, 2025)
Income smoothing is an action carried out deliberately to reduce profit fluctuations in carrying out company per-formance reporting, so that it appears stable and healthy in the eyes of investors. This research aims to obtain em-pirical evidence about the influence of audit quality, return on assets, and net profit margin on income smoothing with financial leverage as a moderating variable. The sample in this research uses secondary data obtained from the financial reports of companies in the consumer goods industry sector listed on the Indonesian Stock Exchange (BEI) from 2020 to 2023. This type of research is quantitative research. The sampling method used purposive sampling and 20 companies were sampled during the 4 years of research with a total of 80 observation data. The analysis technique used in this research is using logistic regression analysis with the help of SEM-PLS 2024 soft-ware. The results of this research partially show that audit quality, return on assets and financial leverage have a significant and influential effect on income smoothing practices, while net profit margin has no effect on income smoothing and financial leverage cannot strengthen the relationship between audit quality, return on assets and net profit margin on income smoothing.